The eye of minds - Dashner, James, 1972- (New York : Delacorte Press, 2013)
"Michael is a skilled internet gamer in a world of advanced technology. When a cyber-terrorist begins to threaten players, Michael is called upon to seek him and his secrets out"--Provided by publisher.
790
Keywords: Computer games -- Juvenile fiction; Virtual reality -- Juvenile fiction; Cyberterrorism -- Juvenile fiction; Terrorism -- Juvenile fiction; Science fiction